2018
DOI: 10.1556/2050.2018.0002
|View full text |Cite
|
Sign up to set email alerts
|

Higher scores on the Mini-K life history battery are associated with greater disgust sensitivity on the three domains of disgust scale

Abstract: Abstract. Disgust is a universal emotion that promotes protective behaviors in three distinct domains: sexual, moral, and pathogenic. There is considerable individual variation in sensitivity to disgust, and past research suggests individuals with slower life history strategies are more sensitive to stimuli that provoke pathogen and moral disgust. We hypothesized that such individuals would also be more sensitive to disgust in a sexual context. Two hundred seventyseven participants completed the Mini-K Life Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Those who benefit from maintaining stable, cohesive groups may favor monogamy and condemn CNM to the extent that multi-partner mating can produce transient relationships, social conflict, and disease transmission; although, as noted, these traits do not necessarily describe individuals in modern CNM relationships. Given existing evidence that CNM relationships are not shortlived (Mogilski et al, 2017;Séguin et al, 2017), can improve relationship satisfaction and functioning (Rodrigues et al, 2016;Levine et al, 2018;Stults, 2018;Fairbrother et al, 2019), and are no more likely to involve unsafe sexual practices than monogamous relationships (Conley et al, 2012(Conley et al, , 2013bLehmiller, 2015), we suspect that moral stigma toward CNM originates from an increasingly defunct intuitive association between sexually promiscuous mating and interpersonally deleterious fast life history traits (Moon et al, 2018). This mismatch (Li et al, 2018) may be driven by modern CNM ethical practices which reduce sources of interpersonal conflict within multi-partner mating systems (e.g., intrasexual competition, jealous anxiety, partner abandonment, child neglect, and disease transmission).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who benefit from maintaining stable, cohesive groups may favor monogamy and condemn CNM to the extent that multi-partner mating can produce transient relationships, social conflict, and disease transmission; although, as noted, these traits do not necessarily describe individuals in modern CNM relationships. Given existing evidence that CNM relationships are not shortlived (Mogilski et al, 2017;Séguin et al, 2017), can improve relationship satisfaction and functioning (Rodrigues et al, 2016;Levine et al, 2018;Stults, 2018;Fairbrother et al, 2019), and are no more likely to involve unsafe sexual practices than monogamous relationships (Conley et al, 2012(Conley et al, , 2013bLehmiller, 2015), we suspect that moral stigma toward CNM originates from an increasingly defunct intuitive association between sexually promiscuous mating and interpersonally deleterious fast life history traits (Moon et al, 2018). This mismatch (Li et al, 2018) may be driven by modern CNM ethical practices which reduce sources of interpersonal conflict within multi-partner mating systems (e.g., intrasexual competition, jealous anxiety, partner abandonment, child neglect, and disease transmission).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to those in monogamous relationships, CNM individuals report experiencing less emotional jealousy (Mogilski et al, 2019), and spend less time actively trying to retain their mate (Mogilski et al, 2017(Mogilski et al, , 2019, which may alleviate conflict in relationships where one or both partners desire extradyadic intimacy. Indeed, people with an unrestricted sociosexuality report greater satisfaction within CNM relationships than they do in monogamous relationships (Rodrigues et al, 2016;Fairbrother et al, 2019), and report less preoccupation with constraining relationship forces (i.e., feeling obligation rather than desire toward a partner), which is associated with greater self-reported quality of life (Rodrigues et al, 2019). Stults (2018) also found that gay and bisexual men involved in multi-partner mating reported that the conflict resolution strategies of CNM improved their relationship satisfaction, communication, and trust.…”
Section: Cnm Morality and Sexual Ethicsmentioning
confidence: 99%